Ethnomedicine of Medicinal Plants in Napa sub-district, South Angkola district, South Tapanuli district - Rambe, Muhammad Arsyad E; Harahap, Cory; Rangkuti, Juni Andriani (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2023)
Ethnomedicine as a method that can be used to explore the use of medicinal plants can be the first step to developing new medicines. The aim of this research is to find out the types of plants used by the people of Napa Village, South Angkola District, South Tapanuli Regency, how to use medicinal plants, and which parts of the plants are used for medicine. Data collection was carried out through observation and interviews. Data was obtained from 5 informants who met the inclusion criteria consisting of 1 traditional leader, 1 health cadre, 1 herbal medicine seller, 2 community leaders. The results of the research obtained data on 35 plants used by the people of Napa Village as medicine. The leaves are the most widely used part. The Ethnomedicine as a method that can be used to explore the use of medicinal plants can be the first step to developing new medicines. The aim of this research is to find out the types of plants used by the people of Napa Village, South Angkola District, South Tapanuli Regency, how to use medicinal plants, and which parts of the plants are used for medicine. Data collection was carried out through observation and interviews. Data was obtained from 5 informants who met the inclusion criteria consisting of 1 traditional leader, 1 health cadre, 1 herbal medicine seller, 2 community leaders. The results of the research obtained data on 35 plants used by the people of Napa Village as medicine. The leaves are the most widely used part. The most widely used processing method is boiling. The Napa Village community uses plants as medicine. Keywords: Ethnomedicine, Plants, Medicine, Napa Village most widely used processing method is boiling. The Napa Village community uses plants as medicine. Keywords: Ethnomedicine, Plants, Medicine, Napa Village